2017
DOI: 10.1249/mss.0000000000001131
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the Neighborhood Environment Walkability Scale for Africa

Abstract: Purpose Development of valid measures of built environments relevant for physical activity is an important step toward controlling the global epidemic of physical inactivity-related noncommunicable diseases and deaths. This study assessed the construct validity of a self-report neighborhood environment walkability scale adapted for Africa (NEWS-Africa), by examining relationships with self-reported walking for transportation and recreation using pooled data from six sub-Saharan African countries. Methods NEW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
0
30
1
Order By: Relevance
“…International data indicate that built environments play important roles in physical activity in general populations of adults 41 There are limited data showing that built environments also are relevant to physical activity in LMICs 41 and specifically in Africa 33 , though there may be some distinct findings in LMICs 33 . The present study adds important evidence that recreation facilities, mixed land use, informal walking paths, and presence and quality of sidewalks are significantly related to physical activity and/or sedentary time in the heretofore unstudied population of African adults with mental or behavioral health disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…International data indicate that built environments play important roles in physical activity in general populations of adults 41 There are limited data showing that built environments also are relevant to physical activity in LMICs 41 and specifically in Africa 33 , though there may be some distinct findings in LMICs 33 . The present study adds important evidence that recreation facilities, mixed land use, informal walking paths, and presence and quality of sidewalks are significantly related to physical activity and/or sedentary time in the heretofore unstudied population of African adults with mental or behavioral health disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Cameroon, Ghana, Mozambique, Nigeria, South Africa, and Uganda) study demonstrated that the NEWS-Africa is a reliable 32 and valid 33 questionnaire to measure built and social environment attributes with relevance to physical activity. It has been tailored to the African context through extensive local input 33 (strongly agree). The one question on residential density reflected common housing patterns in urban and rural areas of Africa, and responses ranged from 1 (lowest density; e.g., few residential buildings/dwellings) to 6 (highest density; e.g., densely packed small houses, settlements, slums).…”
Section: Neighborhood Environment Walkability Scale For Africa (News-mentioning
confidence: 97%
See 1 more Smart Citation
“…The Neighborhood Environment Walkability Scale-Abbreviated version (NEWS-A) is one of the most commonly used self-evaluation questionnaires aiming at measuring people's perceived neighborhood environmental attributes related to physical activity. It was initially applied in developed countries, including the USA and Australia [49,50], and has been widely validated in different countries and cities [51][52][53][54]. The pilot study we first undertook initially adapted the NEWS-A questionnaire on the basis of literature review and on-site observations.…”
Section: Questionnaire Design and Samplingmentioning
confidence: 99%
“… 9 Our knowledge of the social, biological and environmental determinants of physical activity in Africa, including the impact of urbanisation and economic development, is limited by the need for context-specific measures for these determinants and the paucity of longitudinal data to determine causation. 21 Smart phone ownership in Africa is accelerating: a median of 33% reported owning a smart phone in 2018, with a 14%–15% increase in ownership reported in Senegal, South Africa and Ghana between 2015 and 2017. 22 This and the increasing availability of commercial physical activity monitors presents an opportunity to harness physical activity data collected as users carry out their daily lives.…”
Section: Improving Our Evidence Base Through the Objective Measuremenmentioning
confidence: 99%